Identification of bird pests on several sorghum genotypes during the rainy season, in Gunung Kidul, Indonesia - Mugiasih, Ani; Suwitono, Bayu; Gunawan, Achmad; Widyayanti, Setyorini; Muazam, Arif (Universitas Lampung, 2025)
Birds are among the most significant vertebrate pests affecting sorghum crops worldwide, particularly in community farming systems. Their attacks can lead to substantial yield losses, especially during the grain ripening stage. This study aimed to identify the species, number of individuals, attack frequency, extent of crop damage, and control efforts related to bird pests in sorghum cultivation. The research was conducted from December 2022 to February 2023 in Karangmojo Village, Gunungkidul Regency, Yogyakarta, Indonesia. Six sorghum genotypes were planted: bioguma (V1), plonco (V3), samurai (V4), kawali (V6), hitam wareng (V8), and ketan merah (V9). However, observations were focused on bioguma and plonco, which experienced the most bird attacks. Three seed-eating bird species were identified: Geopelia striata (kutut, 156 individuals), Lonchura leucogastroides (bondol jawa or emprit, 375 individuals), and Spilopelia chinensis (derkuku or tekukur, 329 individuals). The peak bird activity occurred in the morning, with 47 attack events recorded in bioguma and 35 in plonco. The average crop damage reached 1.26% in bioguma and 1.24% in plonco, resulting in estimated yield losses of Rp. 922,140.00 and Rp. 750,360.00 per ha, respectively. Control measures employed by farmers included the use of perforated plastic hoods and safety nets, though their effectiveness was limited.